Causal role of immune cells in uveitis: a Mendelian randomization study - Pu, Jianping; Zhao, Zhuanghong; Duan, Yanping; Lu, Jun; Yao, Yuchen; Wen, Yuxin; Li, Yanxun; Zhang, Yu; Ye, Fengyu (Frontiers in Medicine, 2024)
Background: Uveitis refers to a group inflammation affecting the uvea, retina, retinal blood vessels as well as vitreous body, which is one of the common causes of blindness. There is growing evidence linking different types of immune cells to uveitis, although it remains uncertain if these associations imply causal relationships. Recent advancements in high-density genetic markers like SNPs or CNVs for genotyping, along with the progress in genome-wide association studies (GWAS) technologies, have improved our understanding of the immunological mechanisms involved in ocular diseases. Therefore, our objective was to investigate the potential causal link between immune cells and uveitis using a Mendelian randomization study.The exposure and outcome GWAS data for this study were sourced from an open-access database (https://gwas.mrcieu.ac.uk/). Two-sample MR analysis was utilized to evaluate the causal relationship between 731 immune cell features and uveitis. Various MR methods were employed to reduce bias and obtain dependable estimates of the causal link between the immune cell variables and the outcomes. Instrumental variable selection criteria were carefully chosen to enhance the accuracy and efficacy of the causal relationship between different immune cell types and the risk of uveitis.Results: Using two-sample MR, IVW modeling showed that GAD had significant effect on immunophenotypes. CD3 levels on CD45RA-CD4+ T cells (OR=1.087, 95%CI=1.029 1.147, P=0.003) and CD3 levels on CM CD4+ T cells (OR=1.086, 95%CI=1.033 1.141, P=0.001) were found to be elevated in cases of uveitis. HLA DR levels in CD14-CD16+ monocyte cells (OR=0.735, 95% CI=0.635 0.850, P<0.001) and HLA DR levels in NK cells (OR=0.910, 95% CI=0.851 0.972, P=0.005) were observed to be reduced in individuals with uveitis. Furthermore, Two cells were identified to be significantly associated with uveitis risk: HLA DR on in NK cells (OR=0.938, 95%CI=0.899 0.979, P=0.003), HLA DR on CD14-CD16+ monocytes (OR=0.924, 95%CI=0.878 0.972, P=0.002).This study highlights the intricate relationship between immune cells and generalized anxiety disorder using genetic methods, offering valuable insights for future clinical investigations.